Implementation of Mayor Regulations of Probolinggo Number 20 of 2021 concerning the School Budget Activity Plan Application Program (ARKAS) at the Education and Culture Service - Marwiyah, Siti; Puspita, Renny Candradewi; junaidi, Tri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This article aims to explain how to implement the school budget activity plan application (ARKAS) in Probolinggo City. This ARKAS application has been implemented in the Probolinggo City Education and Culture office and is used to improve service quality. To increase educational resources needed for school development and RKAS can also function for the government as a monitoring and evaluation tool for school development. This research aims to determine the implementation of accountability reports regarding school financing every year in Probolinggo City. This research uses descriptive qualitative methods with data collection techniques through in-depth interviews. Researchers conducted interviews with 5 employees who understood ARKAS and several parents at elementary schools in Probolinggo City. The implementation of the ARKAS application information system at the Department of Education and Culture in Probolinggo City includes: 1) resources as constituents in the form of funds and equipment as well as all parties involved in the regional government to monitor the budget system and simplify the service system; 2) bureaucratic structure as a determinant of budget programs in planning activities involving all parties in the school in order to successfully prepare and create an environmentally friendly environment; 3) the character of policy implementation as a determinant of budget guidelines in the education budget as a planning tool, namely planning supervision of educational institutions to obtain fast service; 4) environmental characteristics as a determinant of budget guidelines and includes openness of information providing services with an easy and reliable system.